ANALISIS TIMER DAN SENSOR SUHU TUBUH BAYI PADA PERALATAN PHOTOTHERAPY BERBASIS ARDUINO UNO - Aruan, Dyna Grace Romatua; Siallagan, Wilson; Avisienna (JURNAL MUTIARA ELEKTROMEDIK, 2022)
Jaundice (Neonatal Jaundice) or better known as Jaundice in newborns is a normal thing and usually occurs 1-2 weeks after the birth of the baby. Based on statistics, 60% of the number of newborns look yellow less than 24 hours after the birth of the baby which indicates that the level of bilirubin in the blood is high. This condition is called hyperbiliruinemia. Hyperbilirubinemia is the term used for neonatal jaundice after laboratory results show an increase in bilirubin levels. Bilirubin is the result of the breakdown of hemoglobin due to damaged red blood cells and requires immediate medical attention. If left untreated, excess bilirubin in the blood can enter the brain and damage the brain. Yellow color in babies is usually seen on the forehead and the whites of the eyes, then down to the body, arms and legs. One of the most common medical treatments to cure jaundice is using Phototherapy. Basically babies who suffer from jaundice will be irradiated with blue light which has a long range of 400-510 nm for a certain period of time until their Bilirubin level drops to a level that is safe for the baby.